ANALISIS KEBUTUHAN MODUL MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN GENERALISASI MATEMATIS SISWA SMP - Nirfayanti Nirfayanti; Hamsu Abdul Gani; Mustafa Mustafa (STKIP Andi Matappa, 2023)
The purpose of this research is to analyze the need for mathematics textbooks that can improve the mathematical generalization abilities of class VIII students of SMPN 32 Makassar according to the cooperative learning model. This research is a descriptive qualitative research with research subjects of class VIII students of SMP Negeri 32 Makassar, and Mathematics teachers. Research data was collected through tests of mathematical generalization abilities, interviews and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results showed: (1) the mathematics books used were not in accordance with core competencies, basic competencies, competency achievement indicators, and the existing questions were considered difficult by students; (2) lack of understanding of the learning model applied in math books. So that textbooks are needed in the form of modules that can improve mathematical generalization abilities in students with cooperative learning models; teachers and students state that they need textbooks in the form of math modules that can be understood, motivated in learning, there are many models of real questions so that students agree and support the creation and development of math modules to improve mathematical generalization abilities; (3) the learning model applied is not in accordance with the characteristics of the students; and (4) students' mathematical generalization ability is low because they are not used to being given questions on tests of mathematical generalization ability.